Philippine medical thesaurus on anatomy body regions - Siapno, Joanna O.; Tarlit, Rodolfo Y. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2003)
Realizing the need to organize medical information, a group of researchers decided to initiate the creation of a thesaurus. This idea led to the establishment of the Philippine Medical Thesaurus Project in collaboration with the Medical Informatics Unit (MIU) of the University of the Philippines Manila College of Medicine (UPMCM). It is a long-term project which will include a series of studies and will take years of completion. As such, this paper on `Body Regions' of Anatomy is one of the series. The language chosen was Tagalog since it was considered the best studied Philippine language.
The study commenced by gathering medical terms from the Medical Subject Headings (MeSH) website, which have complete data including term relationships. The terms were first translated using translation tools (such as dictionaries and glossaries) ranked and suggested by the authorities of the topic. Through lexicography, or the use of informants who are first language speakers of Bulacan-Tagalog, terms were validated. Five medical professionals and two non-medical professionals were involved in this study. The former verified more on the technicality of the term while the later is on its' usability.
From the seventy-two (72) MeSH terms gathered, sixty-one (61) have equivalent Tagalog translations, two (2) have definitions only and eleven (11) have no translations. A list of policies and guidelines was formulated to solve some issues of translation before coming up with the final thesaurus entries.
This study shows a satisfactory result but still requires improvement. There are pressing matters which need to be the concerns of future studies.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Human anatomy; Filipino language -- Medical Filipino